Metabolic compounds of biocontrol agents from organic inputs for managing chilli anthracnose caused by Colletotrichum acutatum - Manoranjitham , S K; Naveen , K K; Darshan, K; Sendilvel , V; Rajendran , L; Shanmugapriya , D; Arulsia, A (Plant Science Today, 2025)
Chilli anthracnose caused by Colletotrichum acutatum L. is a major constraint to crop yield and quality. This study, 35 bacterial isolates were obtained from four organic bio-inputs, Panchagavya, Jeevamruth, fish amino acid, and Arappu buttermilk extract, to develop a biocontrol agent against this disease. These isolates were biochemically and molecularly confirmed to be Bacillus spp. The isolates were evaluated for antagonistic potential and plant growth-promoting activity through in vitro assays. Most effective Bacillus isolates (PG12 and PG2) were analyzed using thin-layer chromatography, revealing antibiotics such as iturin (Rf = 0.3) and surfactin (Rf = 0.7). These compounds were further confirmed by PCR amplification of specific genes, producing amplicons of 647 bp and 620 bp, respectively. Gas chromatography-mass spectrometry (GC-MS) analysis identified antimicrobial volatile compounds such as fatty acids, lipopeptides, peptides, and aldehydes in these isolates. The effectiveness of these potent isolates against C. acutatum was compared with the existing bioagent (Pseudomonas fluorescens) and botanicals (e.g., Neem) under greenhouse and field conditions using various combinations. The potent isolates of B. subtillis proved effective in minimizing damage caused by chilli anthracnose in pot culture and natural conditions. The existing study focuses on adopting these isolates in commercial formulation with increased efficacy and shelf life to increase farmers' income.